RNA polymerase: in search of promoters. (15th July 2013) - Feklistov, Andrey
Abstract : Transcription initiation is a key event in the regulation of gene expression. RNA polymerase (RNAP), the central enzyme of transcription, is able to efficiently locate promoters in the genome, carry out promoter opening, and initiate RNA synthesis. All the substeps of transcription initiation are subject to complex cellular regulation. Understanding the molecular details of each step in the promoter‐opening pathway is essential for a complete mechanistic and quantitative picture of gene expression. In this minireview, primarily using bacterial RNAP as an example, I briefly summarize some of the key recent advances in our understanding of the mechanisms of promoter search and promoter opening.